2023
DOI: 10.1161/hypertensionaha.122.20262
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal Morphine Exposure Increases Cardiovascular Disease Risk and Programs Neurogenic Hypertension in the Adult Offspring

Abstract: Background: The opioid overdose and opioid use disorder epidemics are concomitant with increased metabolic and CVD risk. Although opioid use disorder causes adverse pregnancy outcomes, the offspring’s cardiovascular health is understudied. We hypothesized that offspring exposed to morphine in utero would show increased CVD risk factors and endogenous opioid system dysregulation. Methods: Sprague Dawley dams were treated with saline (vehicle, n=10) or es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 80 publications
0
3
0
Order By: Relevance
“…MTD exposure can elevate the cardiovascular risk of cardiac septal defects and congenital long QT syndrome or other arrhythmias [ 43 , 53 ]. Additionally, rat experiments have shown that prenatal morphine exposure increases the risk of hypertension in adult life, with the increase in mean arterial pressure correlating with higher levels of in vivo angiotensin II, inducing vasoconstriction [ 101 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MTD exposure can elevate the cardiovascular risk of cardiac septal defects and congenital long QT syndrome or other arrhythmias [ 43 , 53 ]. Additionally, rat experiments have shown that prenatal morphine exposure increases the risk of hypertension in adult life, with the increase in mean arterial pressure correlating with higher levels of in vivo angiotensin II, inducing vasoconstriction [ 101 ].…”
Section: Discussionmentioning
confidence: 99%
“…The rate of clearance for clonidine is lower in newborns than in adults, peaking at 50% within two months and 90% at one year postnatal age [ 101 ]. The maturation of CYP2D6 may be involved, as the enzyme’s activity in the first week of life decreases, particularly in premature infants [ 110 ].…”
Section: Discussionmentioning
confidence: 99%
“…mRNA was extracted from frozen eWAT and kidney cortex using the Aurum Total RNA Mini Kit (Bio‐Rad Laboratories, Hercules, CA) and iScript Reverse Transcriptase (Bio‐Rad Laboratories) to generate cDNA as previously reported. 27 The quantitative reverse transcription polymerase chain reaction protocol used was: (1) 50 °C 10 minutes; (2) 95 °C 5 minutes; (3) 95 °C 10 seconds; (4) 60 °C 30 seconds; (5) repeat steps 3 to 5 for 45 cycles; (6) 95°C 10 seconds; (7) melt curve 65 °C to 95 °C, increment 0.5 °C for 5 seconds. Primers were designed and validated to determine expression of 18s=F: 5′‐AGTCGGCATCGTTTATGGTC‐3′, R: 5′‐CGAAGCATTTGCCAAGAAT‐3′; ACE=F:5′‐GGAGTACTTCCAACCGGT‐3′, R: 5′‐GCCTTGGCTTCATCAGTC‐3′; ACE2=F: 5′‐TCCAGACTCCGATCATCAAGC‐3′, R: 5′‐GCTCATGGTGTTCAGAATTGTGT‐3′; renin=F: 5′‐CTCTCTGGGCACTCTTGTTGC‐3′, R: 5′‐GGGAGGTAAGATTGGTCAAGGA‐3′; AGT=F: 5′‐GTACAGACAGCACCCTACTT‐3′, 5′‐CACGTCACGGAGAAGTTGTT‐3′; and AT1Rs (angiotensin type 1 receptors)=F: 5′‐CGAAGCGATCTTACATAGGTG‐3′.…”
Section: Methodsmentioning
confidence: 99%